Internet financial reporting by Malaysian preparers / Mohd Noor Azli Ali Khan and Noor Azizi Ismail - Ali Khan, Mohd Noor Azli; Ismail, Noor Azizi (2012)
This research seeks to provide valuable new insight into the issue of various aspect of Internet Financial Reporting (IFR) by Malaysian preparers companies listed on the Main Board of Bursa Malaysia. Perceptions of factors and benefits in using this new technology for financial reporting were also examined. The perceptions of preparers of financial information were solicited using a survey mailed questionnaire. The findings of this study suggested three main benefits to companies that engage in IFR: attract foreign investors, promote company to the public, and attract local investors. The findings also revealed that three main benefits to the users who collect financial information of companies via their website are: increases timeliness and efficiency in obtaining financial information, helps users in the decision making process, and provides another medium of disclosure. The findings suggested three factors that are perceived as important by responding firms to engage in IFR: enhance corporate image, company teller with the technology development, and competitors in the industry. The findings also revealed three factors that inhibit firms from engaging in IFR: need to keep information updated to be of use, required expertise from the company, and concern over security of information. Finally, plausible implications of the findings of the study are then presented and future research will also be discussed.